Bahamas. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in the Bahamas during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as plant health, financing, workshops, agribusiness, scholarships, project management, food security and animal nutrition. Likewise, technical assistance was provided in trade, aquaponics, livestock, planting and food safety. Finally, technical cooperation was provided for the improvement of peasant organizations, backyard gardening, inclusion of women and youth in agriculture.